2015
DOI: 10.1186/s12863-015-0295-8
|View full text |Cite
|
Sign up to set email alerts
|

The chromosomal constitution of fish hybrid lineage revealed by 5S rDNA FISH

Abstract: BackgroundThe establishment of the bisexual fertile fish hybrid lineage including the allodiploid and allotetraploid hybrids, from interspecific hybridization of red crucian carp (Carassius auratus red var. 2n = 100, 2n = AA) (♀) × common carp (Cyprinus carpio L. 2n = 100, 2n = BB) (♂), provided a good platform to investigate genetic relationship between the parents and their hybrid progenies.ResultsThe chromosomal inheritance of diploid and allotetraploid hybrid progenies in successive generations, was studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 30 publications
(28 reference statements)
3
18
0
Order By: Relevance
“…The first of these fragments has been sequenced and published in the GenBank (Zhu, Ma, & Gui, 2006). The latter 5S rDNA gene class, with an approximate length of 200 bp shown in C. gibelio in the present study, has also been reported in C. auratus, but the authors did not provide any discussion involving this rDNA fragment (He et al, 2012, Zhang et al, 2015.…”
Section: Discussionmentioning
confidence: 58%
“…The first of these fragments has been sequenced and published in the GenBank (Zhu, Ma, & Gui, 2006). The latter 5S rDNA gene class, with an approximate length of 200 bp shown in C. gibelio in the present study, has also been reported in C. auratus, but the authors did not provide any discussion involving this rDNA fragment (He et al, 2012, Zhang et al, 2015.…”
Section: Discussionmentioning
confidence: 58%
“…Chromosomal mapping of rDNA clusters has repeatedly helped to unveil diverse evolutionary issues (e.g., [82,83]). Particularly in fishes, it provided valuable clues about the incidence of cryptic, morphologically indistinguishable sibling species [5,6,8,10,84], polyploidization and interspecific hybridization events [85,86], a geographical gradient of genomic and morphological change [87], patterns of sex chromosome differentiation [80,[88][89][90], and the correlation of genome dynamics in response to environmental cues [91,92]. Among the Nannostomus species investigated here, chromosomal mapping revealed somewhat uniform patterns of distribution for both rDNA classes, with one to few sites of accumulation, as found in most fishes [93,94], as well as in some other lebiasinids [21,22] investigated to date.…”
Section: Discussionmentioning
confidence: 99%
“…Chromosome preparations were carried out as described previously [18]. FISH was performed according to the method described by Masaru and Hideo with minor modifications [17].…”
Section: Methodsmentioning
confidence: 99%